ADSORPTION OF ORGANIC MATTER FROM PEAT WATER BY USING GOETHITE AS ADSORBENT - BT FAZLI , NURULAIN FATEHAH (Universiti Teknologi PETRONAS, 2018)
Peat soil is found widely in the coastal areas of Peninsular Malaysia. However, peat is an organic soil with high in organic content and shows the present of humus substances when it gives a dark brown colour to the water and very acidic. Therefore, there is a need to find suitable treatment of peat water before it can be consume or use. In this study, the treatment of peat water was carried out using adsorption process. The adsorbent preparation was done by process of heat treatment (500°C) and calcination time (60 min) then sieve (2.0 - 2.36 mm). The parameters affecting organic matter removal studied were adsorbent dosage (0.5g – 2.5g), temperature (40°C – 80°C), contact time (10 min – 120 min) and initial peat water concentration (20% – 100% of peat water). From the results obtained, the treatment of peat water using goethite give the outstanding results for all parameters which are pH (6.70), colour (90%) and COD (80%). The goethite used in this study shows high potential to be used as an adsorbent for the peat water treatment.